Implementasi Pasal 96 Undang-Undang Nomor 3 Tahun 2020 Tentang Pertambangan Mineral dan Batubara Terhadap Pelaksanaan Reklamasi Lahan Bekas Aktivitas Galian C Ilegal di Kabupaten Sampang - Saskia Andhita; Zilda Khilmatus Shokhikhah (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to find out whether reclamation has been carried out on land used by illegal C/rock excavation activities in Sampang Regency. The author uses empirical methods to answer the problems raised in the research. In fact, the reclamation implementation was not carried out because the Regency/City Government no longer had the authority regarding land restoration efforts. Not knowing whether entrepreneurs are carrying out illegal excavation activities in a certain place and the transfer of authority also limits the local government's space in supervising these activities, resulting in a detrimental impact on the region. The Regency/City Government always makes efforts to report to the Provincial Government and Provincial DLH so that illegal mining can be dealt with because it can pollute the environment. As well as providing advice to the local community about the dangers of illegal C excavation.